2021
DOI: 10.1093/ageing/afab220
|View full text |Cite
|
Sign up to set email alerts
|

Is comprehensive geriatric assessment hospital at home a cost-effective alternative to hospital admission for older people?

Abstract: Background hospital level healthcare in the home guided by comprehensive geriatric assessment (CGA) might provide a less costly alternative to hospitalisation for older people. Objective to determine the cost-effectiveness of CGA admission avoidance hospital at home (HAH) compared with hospital admission. Design/intervention a cost-effectiveness study alongsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 31 publications
1
48
0
Order By: Relevance
“…The authors report lower unadjusted mean cost in the HaH group (-$5054). This is consistent with a recent economic analysis of a multisite randomised controlled trial of HaH in the UK 5…”
Section: Cost Of Home Hospitalization Vs Inpatient Hospitalization In...supporting
confidence: 91%
“…The authors report lower unadjusted mean cost in the HaH group (-$5054). This is consistent with a recent economic analysis of a multisite randomised controlled trial of HaH in the UK 5…”
Section: Cost Of Home Hospitalization Vs Inpatient Hospitalization In...supporting
confidence: 91%
“…Outpatient parenteral antibiotic therapy (OPAT) has shown excellent results despite the use of broader selection criteria than those recommended by IDSA [ 10 ] in the recently published experience of the GAMES cohort [ 122 ]. However, OPAT at home, despite being a cost-effective alternative for older people [ 123 ], is not available in most settings, and age-related conditions also complicate attendance at day hospitals for this purpose. The partial oral treatment of endocarditis in clinically stable patients after initial intravenous antibiotic therapy has been shown to be non-inferior to continued intravenous antibiotic treatment in patients (including those ≥ 65 years old) with left heart endocarditis [ 124 , 125 ], also after a 5-year follow-up period [ 126 ].…”
Section: Antibiotic Treatment: the Shorter The Better Diminishing Int...mentioning
confidence: 99%
“…To our knowledge, only a few studies have investigated the efficacy or effectiveness of being treated at home for acute illness versus being hospitalised in a European context, and no studies in a Danish context. Shepperd et al found in a randomised controlled trial (RCT) that a home hospital model for older people provided an alternative to hospitalisation,9 and that hospital at home services can be a cost-effective alternative to hospital admissions for selected older people 10. In the USA, Levine et al compared a home-hospital model with usual hospital care and found that home-hospital care reduced costs, healthcare use and readmissions while increasing physical activity compared with usual hospital care 11.…”
Section: Discussionmentioning
confidence: 99%
“…Shepperd et al found in a randomised controlled trial (RCT) that a home hospital model for older people provided an alternative to hospitalisation, 9 and that hospital at home services can be a cost-effective alternative to hospital admissions for selected older people. 10 In the USA, Levine et al compared a home-hospital model with usual hospital care and found that home-hospital care reduced costs, healthcare use and readmissions while increasing physical activity compared with usual hospital care. 11 In a qualitative evaluation nested in the same RCT, 11 the results showed that compared with usual hospital care, patients treated at home had better experiences with their care team (nurses and physicians), better sleep, increased physical activity and better experiences with system factors such as admissions processes.…”
Section: Discussionmentioning
confidence: 99%